If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 + -1(5x + -3) = -1 Reorder the terms: 3x + 1 + -1(-3 + 5x) = -1 3x + 1 + (-3 * -1 + 5x * -1) = -1 3x + 1 + (3 + -5x) = -1 Reorder the terms: 1 + 3 + 3x + -5x = -1 Combine like terms: 1 + 3 = 4 4 + 3x + -5x = -1 Combine like terms: 3x + -5x = -2x 4 + -2x = -1 Solving 4 + -2x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -1 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -1 + -4 -2x = -1 + -4 Combine like terms: -1 + -4 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| 3x+1-(5x-3)=1 | | 5x+4=6(x-1)+5 | | 9x+5=4x+8+5x | | 3x+12=5x-3 | | 5xa= | | 4n-11+2n=26 | | 0.03x+2.19y=25 | | 64x^3-14x-1=0 | | 7(2x+3)=296 | | 3t+7y-8z-4z+5t= | | 4(3-6x)=9(2x-2) | | 96x^3-16x^2-13x-1=0 | | 5z^2+20=0 | | 3X-2+23X= | | y=85-13.254(2) | | y=85-13.254(1) | | 0.5x-3=0.75x+4 | | x^2+6x-16=416 | | (x^2+7)(x^2-9)= | | (x-2)(2)((x+10)-2)=832 | | 6x+2y-8x+3xy-9y= | | x^2+2x-15=x^2-5x-6 | | 5x+4=6x-1 | | (x-2)((x+10)-2)=416 | | (x-2)((x+10)-x)=416 | | 5x+4=6x-11 | | f(1)=sqrt(4x+28) | | a-2=a^3 | | 2(5-2y)+y=4 | | 16546546*4654= | | y+y=2+18 | | 4p^2+8p^2=0 |